Putting 'Humpty' together again : a testifying of the embodied nature of human experiencing : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Psychology at Massey University, Palmerston North, New Zealand - Tuck, Brian William (Massey University, 2009)
The complex functioning of the human body produces the biological, historical and environmental contingencies of lived existence. These experiences of embodiment are chiasmic, dialectical and dialogical, and underpin the narrative dilemmas we create through the storied nature of our attempts to make sense of them. In testifying my own embodiment this autobiographical form of sensual scholarship emphasizes the subjective basis for my body’s psychology. By developing the complicating action segments of my life story told through interview data into a chronologically-ordered and textually- layered account of personally significant memories, I craft a story of my panicking body. My upbringing was influenced by discourses that reinforced parental and family affiliation at the expense of my feeling body. Unravelling my need to exercise as a contingency of this affiliation provides retrospective meaning to the distress my panicking caused. Situating my feelings, thoughts, emotions and actions within the broader constraints of my family’s history, community, religion and culture reveals the contingent nature of my embodiment. Describing the shifting contingencies of a life lived since my upbringing in the small, rural town of Inglewood, New Zealand, provides the opportunity to recognize and to re-align the dialectics of identity that help to make up my body’s psychology. Juxtaposing this narrative meaning-making are my revelations of experiential integration achieved through the flow of exercise. Understood as an extension of my body’s fundamental sensuality, this evolutionally-refined capacity for engagement underpins my lived experiencing. Together these sentient and reflexive forms of testimony confirm the inherence of my sensuality and the circumstance of self-hood, and invite you, the reader, to explore the workings of your own body. By revealing the sensual and symbolic strands of my embodiment this story of human contingency reveals something of the fleshy consciousness that we all share, not by speaking for anyone else, but by calling attention to the taken-for-granted nature of its unfolding. By arguing for a psychology more relevant to lived experiencing, my thesis questions the body of Western science and, in particular, psychology’s version of it. Articulating the felt nature of my experiencing situates my mind back in my body and, in doing so, fleshes out its psychology. While the insights shared here are personal, the relevance of the felt-body is found in the ways it becomes discoursed and narrated.
Keywords: Exercise (psychological aspects); Autobiography; Fields of Research::380000 Behavioural and Cognitive Sciences::380100 Psychology::380199 Psychology not elsewhere classified